RASIONALITAS MENUJU IMAN DALAM PEMIKIRAN WOLFHART PANNENBERG SERTA SIGNIFIKANSINYA BAGI UMAT KRISTEN MASA KINI - Christian Arisandi Kiding Allo (STT Kingdom, 2023)
Behind the scientific advances that have been produced by enlightenment and modernism, negative impacts soon emerged and then spread to all aspects. Theology which is based on the faith and tradition of the Church is then bombarded by criticism of the rationality and empiricism of modern science. The impact of modernism was so severe that it made Catholics take the policy of proclamation of papal infallibility in 1870 and the policy promoted by Pope Pius X (1903-1914) in order to eradicate every scholar who was considered infected by the disease of modernism. Responding to this problem, Pannenberg emerged as one of the many twentieth-century theologians who both fought against modernism and defended the foundations of Christian theology. Christianity and the age of enlightenment, faith and reason are a unity that should be celebrated equally. Such is the characteristic of Pannenberg, which is very different from the style of theology of Barth, Bultmann, and theologians of his time. Pannenberg’s main accomplishment is that he rehabilitated reason and rationality in theology, so faith is not a hasty leap into irrationality.